Development of a test battery for the soccer goalkeeper - Knoop, M.; Pischetsrieder, H.; Lange, P.; Ferrauti, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Up to now regular performance diagnostics in professional and upper-league amateur soccer have only dealt with the requirement profiles of outfield players. The goalkeeper´s special workload demands in competition and training have not been given enough attention. In order to close this gap we began to develop a specific test battery focused on the offensive and defensive requirements of the goalkeeper in the modern game. Therefore, in accordance to a systematic analysis of all goalkeeper activities during the European Championships 2008, we designed the following tests: • Elementary ability tests: Squat Jump (SJ), Counter-Movement-Jump (CMJ), Foot Tapping (FT) • Complex offensive ability tests: precision and speed of passes, throws and kicks • Complex defensive ability tests: 5 and 10 m sprint, sidestep sprint (SS), reaction and action velocity (RAV) and safe hands (SH). RAV is measured by a self developed measurement system, the "Keepers Time Detector" (KTD 4pro), consisting of a fourfold selected optical signal and four respective defense actions to a fixed and contact sensitive ball (top right, top left, bottom right, bottom left of the goal). We analyze time and split time for singular or multiple defense actions. SH was measured using a ball cannon and a protocol with a stepwise increasing ball velocity. The test battery was applied with seven 1st division teams ("Junioren Bundesliga"). Sixteen junior goal keepers (18.0±0.9 yrs; 187±5 cm; 80.4±7.7 kg) participated in the study. Selected results (mean values, standard deviation) are presented: SJ height (39.4±4.4 cm); CMJ height (47.5±5.8 cm); FT (11.4±1.1 Hz); throwing distance (39.2±3.3 m); speed of kicks (109.9±5.0 km/h); 5 m sprint (1.11±0.05 s) and 10 m sprint (1.87s±0.05 s). Singular RAV in different directions did not correlate very closely, neither to the top left and right angles of the goal (left 1.41±0.07 s vs. right 1.39±0.06 s; r=0.5), nor to the bottom left and right angles (left 1.30±0.05 s vs. right 1.23±0.07 s). The individual results are compared to the collected mean values and specific training recommendations are given to the coaches. Specific differences in the reaction and action velocity (RAV) to the left vs. right or to the top vs. bottom angles, respectively, are analyzed individually. Further detailed analysis of movement processes (footwork, step-sequences, upper body work) are planned focusing on an increasing efficiency of motor solution.